Duality in skepticism: Contrasting judgment and action - Blum, Emily S.; Hatfield, Richard C. (Contemporary Accounting Research, 2025)
Abstract Professional skepticism is an essential element of a healthy audit. In this study, we present a framework in which the two elements of professional skepticism—skeptical judgment and skeptical action—differ in that skeptical judgment involves paying attention to audit risks, whereas skeptical action often involves overcoming personal risks. This distinction suggests that the optimal conditions for skeptical judgment may differ from the optimal conditions for converting that judgment to skeptical action. Specifically, interventions that promote vigilance will facilitate judgment because they make potential accounting issues salient, but such a focus will also draw attention to potential adverse consequences of taking action. To test this proposition, we conduct two studies in which we align skeptical judgment and skeptical action with two pairs of distinct and contrasting mindsets to operationalize differential vigilance. Our results suggest a duality in skepticism which has important implications for researchers and practitioners designing interventions to improve audit quality.